Impact de la situation linguistique minoritaire sur les soins de santé pour des personnes âgées francophones de l'Ontario souffrant de maladies chroniques : une étude qualitative exploratoire - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Consortium national de formation en santé, 2010)

Francophone seniors in Ontario: A health portrait - Bouchard, Louise; Makvandi, E.; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, University of Ottawa, 2014)

Les aînés francophones de l’Ontario : un portrait de santé. - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa, 2014)

The health of the Francophone population aged 65 and over in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

The pathway to diagnosis of dementia for Francophones living in a minority situation - Garcia, Linda J.; McCLeary, L.ynn; Emerson, Victor; Léopoldoff, Hélène; Dalziel, William; Drummond, Neil; Cohen, Carole; Koehn, Sharon; Silvius, James (The Gerontologist, 2014)
Purpose of the Study: As the prevalence of dementia increases, the pressure to make early diagnoses also increases. Although patients must be able to identify the symptoms to access appropriate services, they may not be equally accessible to all citizens in a multicultural society. Health care professionals and patients may lack a common “first language.” This study explores the experience of francophone persons with dementia (PWD) and their caregivers during the peri-diagnostic period. Design and Methods: Individual interviews were undertaken to elicit information regarding symptoms, the role of the family and friends, and the access to formal services. Seven PWD and their caregivers who spoke French as their primary language but who lived in a primarily English-speaking region completed the interviews. Results and Implications: No single symptom seemed sufficient to alert participants that dementia might be present. Participants communicated that there was a dire need to inform the public about the signs of dementia; they spoke of the role of the family physician and the importance of having a long-standing relationship with a health professional. For some, having similar personal characteristics, such as language and culture, might accentuate the strength of the relationship and facilitate the process of diagnosis.

Impact de la situation linguistique minoritaire sur les soins de santé pour les personnes âgées francophones de l’Ontario souffrant de maladies chroniques : partage des connaissances et rétroaction. Rapport de recherche - Lemonde, Manon; Boudreau, Françoise; Dufour, Suzanne (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)